Gender Quotas: Challenging the Boards, Performance, and the Stock Market - Giulia Ferrari; Valeria Ferraro; Paola Profeta; Chiara D. Pronzato (Institute for the Study of Labor (IZA), 2016)
In 2011, Italy introduced gender quotas for boards of directors of companies listed on its stock market. Comparing before and after the reform within firms, we find that quotas are associated with a higher share of female board directors, higher levels of education of board members, and a lower share of older members. We then use the reform period as an instrument for the share of female directors and find no significant impact on firms' performance. Interestingly, we find that the share of female directors is associated with a lower variability of stock market prices. We also run event studies on the stock price reaction to the introduction of gender quotas. A positive effect of the quota law on stock market returns emerges at the date of the board's election. Our results are consistent with gender quotas giving rise to a beneficial restructuring of the board, which is positively received by the market.
Keywords: J20; J48; J78; 330; education; age; financial markets